Collaborative self-translation in the screenplays of The Godfather trilogy. (1st March 2021) - Gefen, Rina; Weissbrod, Rachel
This study examines the adaptation of the novel The Godfather into screenplays by author Mario Puzo and director Francis Ford Coppola. Combining translation and adaptation studies, we regard this adaptation as a case of 'collaborative self-translation', a concept that has so far been rarely applied beyond translations studies, and use a model designed for the study of adaptation to analyse it. However, we expand the model by applying it to screenplays, and examining prequel and sequel, which are mainly present in the second and third screenplays of the trilogy. In addition to calling attention to the screenplay as a vital stage in the transformation of a literary work into a film, this article shows that the adaptation model can be a valuable tool to systematically analyse adapted screenplays, thus expanding the methodological repertoire of both adaptation and screenwriting studies. Moreover, it was found that the combined discussion of adaptation, sequel and prequel may contribute to an understanding of the complex relations between them and the source. Based on these theoretical insights, we show that through merging the creative powers of Puzo and Coppola, the screenplays shed new light on social, family and cultural themes that appear to some extent in the novel, taking the conventions of the crime genre in new and surprising directions.